Elongation of the side chain by linear alkyl groups increases the potency of salacinol, a potent α-glucosidase inhibitor from the Ayurvedic traditional medicine "Salacia, " against human intestinal maltase. (1st February 2021) - Takashima, Katsuki; Sakano, Mika; Kinouchi, Eri; Nakamura, Shinya; Marumoto, Shinsuke; Ishikawa, Fumihiro; Ninomiya, Kiyofumi; Nakanishi, Isao; Morikawa, Toshio; Tanabe, Genzoh
Graphical abstract: Abstract: Four chain-extended analogs (12a –12d ) and two related de- O -sulfonated analogs (13a and 13c ) by introducing alkyl groups (a : R = C3 H7, b R = C6 H13, c : R = C8 H17, d : R = C10 H21 ) to the side chains of salacinol (1 ), a natural α-glucosidase inhibitor from Ayurvedic traditional medicine " Salacia ", were synthesized. The α-glucosidase inhibitory activities of all the synthesized analogs were evaluated in vitro . Against human intestinal maltase, the inhibitory activities of 12a and 13a with seven-carbon side chain were equal to that of 1 . In contrast, analogs (12b –12d, and 13c ) exhibited higher level of inhibitory activity against the same enzyme than 1 and had equal or higher potency than those of the clinically used anti-diabetics, voglibose, acarbose, and miglitol. Thus, elongation of the side chains of 1 was effective for specifically increasing the inhibitory activity against human intestinal maltase.